KORELASI ANTARA KEMAMPUAN MEMAHAMI ISI NOVEL DENGAN KEMAMPUAN MEMAHAMI UNSUR INTRINSIK TERHADAP HASIL BELAJAR APRESIASI SASTRA SISWA SMA NEGERI 1 AMPIBABO KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Mai, Tri Yanti Ramly B. (BAHASANTODEA, 2016)
This research have the purpose to know the correlation ability to understanding novel contents to the literature learning outcomes of the students SMA Negeri 1 Ampibabo, Ampibabo Subdistrict, Parigi Moutong regency; the correlation ability to understanding novel contents with the ability to understanding intrinstic element to the literature appreciation learning outcomes of the students SMA Negeri 1 Ampibabo, ampibabo subdistrict, Parigi moutong regency. This research implemented in the SMA Negeri 1 Ampibabo, Ampibabo Subdistrict, Parigi Moutong regency. The method of this research analyzed by descriptive and data analysis by inferensial. Descriptive analysis include describing, central tendention and disseminating tendention, the distribution composing score frequent and his histogram. Whereas the data analysis by inferensial used to hiphotesis trial utility. The research outcomes showing average score which getting by the twelfth grade student of SMA Negeri 1 Ampibabo parigi moutong regency which have correlation with the ability to understanding the novel contents categoryzed was able, with the average score 75,36. For the second hypthotesis, according to the significant between the ability to understand the intrinstic element with the literature appreciation learning outcomes. The simple crrelation analisys (r) founded correlation between novel contents element understanding and instrinsic element understanding to the literature appreciation learning outcomes of the students SMA Negeri 1 Ampibabo, ampibabo Subdistrict, Parigi Moutong regency (r) is 0,792. There is a positive correlation between the ability to understanding the novel contents with the ability to understanding instrinsic element to the literature appreciation learning outcomes based on the data analysis outcomes can be explain that the ability to understanding the novel contents and the ability to understanding the instrinsic elements to the literature appreciation learning outcomes of the twelfth grade student of SMA Negeri 1 Ampibabo by an individual or a group have a positive correlation. However, the strong with the R score is 82,1%.